Scientific Achievements of the Institute of Geography of the National Academy of Sciences of Ukraine in 2024 - Maruniak, Eu. O.; Chekhniy, V. M. (Ukrainian Geographical Journal, 2025)
The publication’s purpose is to highlight the main scientific achievements of the Institute of Geography of the National Academy of Sciences of Ukraine in research work carried out in 2024. Particular attention is paid to the issues of environmental impact assessment, social transformations at all spatial levels, expansion of international cooperation, and adaptation of the European experience.
Keywords: geography; methodology; methods; recommendations; russian aggression; impacts; consequences